Integrating Biotechnology, Pathological Analyses, and Applied Sciences for Innovations in Health and Environment - Ali Majid Kumail; Zainab Al Hawra Karem Meften; Zeena Hassan Dari; Mustafa Lafta Atshan Aljayashi; Enas Ali Mohammed Thahir (American Journal of Botany and Bioengineering, 2025)
Biotechnology offers transformative potential in addressing global challenges related to health, agriculture, and environmental sustainability. Despite rapid advancements, a significant knowledge gap remains in integrating biotechnological tools with pathological analysis and applied sciences for comprehensive solutions. This interdisciplinary study reviews recent innovations in genetic engineering, molecular diagnostics, nanotechnology, and bioinformatics, with emphasis on their synergistic applications in disease diagnosis, personalized medicine, environmental bioremediation, and sustainable agriculture. Through a comparative analysis of current practices and emerging trends, findings suggest that cross-sector integration enhances diagnostic precision, therapeutic effectiveness, and ecological resilience. Results underscore the need for harmonized regulatory frameworks and ethical standards to guide future applications. The implications point toward a collaborative scientific frontier that bridges biology, technology, and clinical practices for improved public health and environmental outcomes